Prevention of cardiovascular disease in a rural region of India and strategies to address the unmet need. Issue 17 (20th July 2011) - Wood, Anna; Pell, Jill; Patel, Anushka; Neal, Bruce; Raju, P Krishnam; Chow, Clara K
Abstract : Objectives: To determine levels of cardiovascular disease (CVD) prevention and to model the potential impact of improved prevention strategies for a large rural Indian region. Design: A cross-sectional study with modelling of coronary heart disease (CHD) events over 10 years. Setting: Rural Andhra Pradesh, India. Participants: A stratified random sample of 1079 adults 30 years and older. Main outcome measures: Proportion on medical and behavioural treatments for prevention of CVD; estimated number of CHD events using a locally recalibrated Framingham risk equation. Results: Among the 3.5% (95% CI 2.1% to 4.9%) with existing CVD, 49.3% (95% CI 28.8% to 69.8%) were on blood pressure (BP)-lowering medication, 4.7% (95% CI 0 to 10.4%) were on cholesterol-lowering medication, 24.6% (95% CI 9% to 40.3%) had increased exercise and 26.9% (95% CI 2.6% to 51.1%) attempted to quit smoking. Among the 7.6% (95% CI 6.2% to 8.9%) with a high global CHD risk (>20% over 10 years), 29.5% (95% CI 19.5 to 39.5%) were on BP-lowering medication, 2.8% (95% CI 0 to 6.7%) were on cholesterol-lowering medication, 19.4% (95% CI 10.9% to 28%) had increased exercise and 24.8% (95% CI 15.8% to 33.8%) attempted to quit smoking. If confirmed drug therapies were provided to all individuals at high risk there would be a 28% reduction in cardiovascular events over 10 years at an approximate annual treatment cost of US$533 per event avoided. Conclusions: There are serious deficiencies in CVD prevention in rural areas of India. Addressing these with simple confirmed drug treatments could produce a large reduction in the future cardiovascular burden in India.